MANAJEMEN PEMASARAN DALAM MENINGKATKAN KEPUASAN PELANGGAN DI SMP HOLY FAITHFUL OBEDIENT DEPOK - Kota, Aleksander; Budianto, Irawan R.D. (PT. Media Edutama Nusantara, 2024)
ABSTRACT This study aims to determine marketing management in increasing customer satisfaction at Holy Faithful Obedient Junior High School Depok through a qualitative approach descriptive method with documentation, interviews, and observations as techniques in collecting data. The results show that marketing management through a marketing mix or marketing mix strategy in educational services as a tactical tool for promoting school excellence products with 7Ps (process, pshycal evidence, people, promotion, place, price, and product) has run quite well in increasing customer satisfaction at Holy Faithful Obedient Junior High School Depok. The increasing number of learners every year is proof of this statement. There are three elements that dominate the marketing mix in influencing customer satisfaction such as excellent academic and non-academic programs. But the output results have not been as expected. The costs that must be incurred are community participation or donations of education costs from the results of meetings between parents, guardians and the school and some free fees provided by the government. Holy Faithful Obedient Junior High School Depok is a school located in the city of Depok.Holy Faithful Obedient Junior High School Depok carries out learning programs based on the Independent Curriculum for Grade VII and the 2013 Curriculum applies to grades VIII and IX.